2021
DOI: 10.3390/jcm10153368
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Pneumonia: Outcomes and Characteristics of Patients in an Inner-City Area after 3 Months of Infection

Abstract: Background: The morbidity and long term pulmonary consequences of COVID-19 infection continue to unfold as we learn and follow survivors of this disease. We report radiological evolution and pulmonary function findings in those patients. Methods: This was a retrospective cohort study of adult patients referred to the post-acute COVID-19 pulmonary clinic after a diagnosis of COVID-19 pneumonia. The study period was after the initial peak of the pandemic in New York City, from June to December 2020. Results: 111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Substantial heterogeneity across studies was observed in each of the three meta-analyses (I 2 =98.8%, 97.4% and 95.9%, respectively; p<0.001). ASADI-POOYA [24] AUL [91] AYDIN [65] BALDINI [62] FERNÁNDEZ-DE-LAS-PEÑAS [105] SUÁREZ-ROBLES [128] DARCIS [101] DREYER [103] ZAYET [137] YOMOGIDA [34] VENTURELLI [135] VARGHESE [134] TAYLOR [131] TAWFIK [14] SZEKELY [66] SULTANA [129] STAVEM [127] SONNWEBER [58] RIGHI [123] PELUSO [13] O'SULLIVAN [122] O'KEEFE [121] NAIK [54] MOTIEJUNAITE [64] MECHI [44] MALLIA [115] KLEIN [111] GABER [106] EROL [25] DIAZ-FUENTES [102] DANKOWSKI [100] CARFI [96] CORTÉS-TELLES [69] CARVALHO-SCHNEIDER [97] BOARI [94] VIJAYAKUMAR [65] Total (I 2 =95.9%, p<0.001) ZHANG [39] D'CRUZ [35] D'CRUZ [35] TODT [132] TAYLOR [131] SKJORTEN [38] DAYNES [10] APARISI [26] DE GRAAF [61] YIN …”
Section: Prevalence Of Post-covid Breathlessness Among Covid-19 Survi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial heterogeneity across studies was observed in each of the three meta-analyses (I 2 =98.8%, 97.4% and 95.9%, respectively; p<0.001). ASADI-POOYA [24] AUL [91] AYDIN [65] BALDINI [62] FERNÁNDEZ-DE-LAS-PEÑAS [105] SUÁREZ-ROBLES [128] DARCIS [101] DREYER [103] ZAYET [137] YOMOGIDA [34] VENTURELLI [135] VARGHESE [134] TAYLOR [131] TAWFIK [14] SZEKELY [66] SULTANA [129] STAVEM [127] SONNWEBER [58] RIGHI [123] PELUSO [13] O'SULLIVAN [122] O'KEEFE [121] NAIK [54] MOTIEJUNAITE [64] MECHI [44] MALLIA [115] KLEIN [111] GABER [106] EROL [25] DIAZ-FUENTES [102] DANKOWSKI [100] CARFI [96] CORTÉS-TELLES [69] CARVALHO-SCHNEIDER [97] BOARI [94] VIJAYAKUMAR [65] Total (I 2 =95.9%, p<0.001) ZHANG [39] D'CRUZ [35] D'CRUZ [35] TODT [132] TAYLOR [131] SKJORTEN [38] DAYNES [10] APARISI [26] DE GRAAF [61] YIN …”
Section: Prevalence Of Post-covid Breathlessness Among Covid-19 Survi...mentioning
confidence: 99%
“…The influential analysis indicated no single study had a major impact on the pooled prevalence estimate (supplementary table 3). [63] BALDINI [62] BELL [92] DARCIS [101] CARFI [96] CARVALHO-SCHNEIDER [97] CORTÉS-TELLES [59] DANKOWSKI [100] DIAZ-FUENTES [102] DREYER [103] EROL [25] GABER [106] GALVÁN-TEJADA [19] ÇALIK KÜTÜKCÜ [95] BOARI [94] MORADIAN [117] MEIJE [56] MAHMUD [114] LANDI [112] JACOBS [109] KLEIN [111] MALLIA [115] COMEBAC STUDY GROUP [85] MOTIEJUNAITE [64] GHOSN [11] GARRIGUES [53] FORTINI [36] BLOMBERG [93] ARNOLD [89] AUGUSTIN [90] ARMANAGE [88] SUÁREZ-ROBLES [128] VIJAYAKUMAR [65] VARGHESE [134] VENTURELLI [135] Subtotal (I 2 =97.8%, p<0.001) Heterogeneity between groups: p=0.014 ZHAO [138] TOSATO [133] SZEKELY [66] TAWLIK [14] TAYLOR [131] SUN [130] SHOUCRI [126] SULTANA [129] STAVEM [127] SONNWEBER ...…”
Section: Prevalence Of Post-covid Breathlessness Among Covid-19 Survi...mentioning
confidence: 99%
“…Results of all included studies can be found in Table S1 . All studies included a population with a mean or median age between 47 and 66 years and most studies had an equal distribution of males and females.The majority of the studies were conducted in Europe (n = 26) [ [3] , [4] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] ],49,51,56,60,62,65,66,67,69,70,74,76,77,79,80,81,83,84], six were conducted in North America [ [59] , [60] , [61] , [62] , [63] , [64] ], four in South America [ [65] , [66] , [67] , [68] ] and eleven in Asia [ [16] , [17] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] ]. The population of the studies varied between 17 and 1733 with a mean of 177 participants.…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that age and severe acute COVID-19 were independently associated with a decrease in DLCO at 3–6 months following COVID-19. Other studies [ 16 , 17 , 39 , 40 ] confirm the association of severe acute COVID-19 and decreased DLCO at follow up, although Fortini et al [ 41 ] and Diaz-Fuentes [ 61 ] did not find an association between severe acute COVID-19 and decreased DLCO. This might be explained by the patient selection since no patients who were admitted to the ICU were included in the cohort of Fortini et al and 20.7% of the included patients were asymptomatic at 3 months post COVID-19 in the cohort of Diaz-Fuentes et al…”
Section: Discussionmentioning
confidence: 96%